TEACHING METHODS OF PRACTICE STYLE AND COMMAND STYLE IN IMPROVING THE SKILL OF BUTTERFLY STROKE - Argantos, A.; Tangkudung, James A.P. (Program Pascasarjana Universitas Negeri Jakarta, 2015)
The objective of this research is to find out different impacts of the teaching methods; practice style and command style. This research is conducted in the Faculty of Sports Science, State University of Padang during the academic year of 2010/2011. The applied research method is an experimental method. The sample consists of 40 (college) students who are divided into 4 groups of 10 persons. The data analysis technique is performed by a two-ways variance analysis followed by the tukey test at the significance level = 0, 05. The results of this research are: 1) in all aspects, the skill of butterfly stroke by the teaching method of command style is better than the practice style, 2) for the students with high motor skills, the skill of butterfly stroke by the teaching method of practice style is better than the command style, and 3) for the students with low motor skills, the skill of butterfly stroke by the teaching method of command style is better than the practice style.